Simultaneous estimation of pyrantel pamoate, praziquantel & febantel by high performance liquid chromatography using dual wavelength - Sajjanwar, Rupali; Bhaskaran, Shyamala; Kakati, Kulesh; Jha, Shailendra Kumar (Journal of Applied Pharmaceutical Research, 2014)
A sensitive, fast, and stability-indicating gradient reverse-phase liquid chromatography method was developed for quantitative simultaneous estimation of Pyrantel pamoate, Praziquantel and Febantel using reverse phase high performance liquid chromatography by gradient elusion with dual wavelength at a specified time interval. All three ingredients were well separated with Phenominax Hypersil C18 (ODS) (4.6 X100mm) 3µm column. The various factors affecting different parameters during method development by HPLC was analyzed and standardized.